To identify two equations from the provided list that form a system with one solution, we need to express each equation in the slope-intercept form (y = mx + b). We will work on equations 4, 5, and 6.
-
Equation 4: \(2y = 6x + 2\)
- To convert it to the slope-intercept form, divide both sides by 2: \[ y = 3x + 1 \] (This equation is already present as equation 3.)
-
Equation 5: \(y - 5x = 2\)
- Rearranging this to slope-intercept form gives: \[ y = 5x + 2 \]
-
Equation 6: \(y - 4x + 1 = 0\)
- Rearranging this to slope-intercept form gives: \[ y = 4x - 1 \]
Now we have:
- Equation 3: \(y = 3x + 1\)
- Equation 5: \(y = 5x + 2\)
- Equation 6: \(y = 4x - 1\)
Next, let's check the slopes of the pairs:
- Slope of Equation 3: \(m_1 = 3\)
- Slope of Equation 5: \(m_2 = 5\)
- Slope of Equation 6: \(m_3 = 4\)
The combinations with different slopes are:
- Equations 5 and 6: \(y = 5x + 2\) and \(y = 4x - 1\) (Their slopes are 5 and 4 respectively, so they intersect at one point.)
- Equations 3 and 5: \(y = 3x + 1\) and \(y = 5x + 2\) (Different slopes, 3 and 5.)
- Equations 3 and 6: \(y = 3x + 1\) and \(y = 4x - 1\) (Different slopes, 3 and 4.)
Therefore, any of the following pairs can be used to form a system with one solution:
- Equations 5 and 6: \(y = 5x + 2\) and \(y = 4x - 1\)
- Equations 3 and 5: \(y = 3x + 1\) and \(y = 5x + 2\)
- Equations 3 and 6: \(y = 3x + 1\) and \(y = 4x - 1\)
Example Pair: \(y = 5x + 2\) and \(y = 4x - 1\) (Equations 5 and 6)